Nanocrystalline silver gel versus conventional silver sulfadiazine cream as topical dressing for second-degree burn wound: A clinicopathological comparison - Gouranga Dutta; Nandini Das; Abhishek Adhya; Kinkar Munian; Bijay Kumar Majumdar (Wolters Kluwer Medknow Publications, 2018)
Background: The use of topical chemotherapy is fundamental to prevent infections thereby reducing local inflammation, pain and early healing in superficial, and deep dermal burns. Among the whole gamut, choice of topical agents became an important decisive factor. Silver sulfadiazine (SSD) cream has been an important part of burns management for many years. The major complications attributed to silver compounds are due to the complex or anion sulfadiazine, not the silver itself. With better understanding of the physical and chemical properties, nanocrystalline silver particles have emerged as the most studied material for burn wound dressing recently. Having in mind the difficulties experienced, the aim of the present study is to compare SSD with nanosilver (nano-Ag) gel dressing to treat second-degree burn wounds. Materials and Methods: Over a period of 24 months, a total of 90 cases were studied. 45 patients randomly included in each group, further divided into two subgroups depending on depth (superficial and deep) and involvement of total body surface area (10%-20% and >20%-30%) to minimize bias. Clinical, microbiological, and histological parameters were analyzed. Results: In NS group, significantly less pain observed throughout the study period in both superficial and deep dermal burn patient. Pseudomonas was the predominant flora. Nano-Ag gel was effective in controlling most of the microorganisms except Klebsiella and Proteus sp. Healthy granulation tissue appeared faster (P = 0.0009) in deep dermal burns in nano-Ag group and confirmed histologically. Overall wound healing was more satisfactory in nano-Ag group for both superficial and deep dermal wounds, clinically as well as by histological examination. Conclusions: Clinical and histological studies showed that nano-Ag gel has a positive impact on overall healing process of the patients and proved more beneficial for the management of partial thickness burn as compared to SSD.